Brazil as an economic superpower? understanding Brazil's changing role in the global economy - Brainard, Lael.; Martinez-Diaz, Leonardo, 1976- (Brookings Institution Press, 2009)
"Scholars and policymakers from Brazil, Europe, and the United States examine the present state and likely future of Brazil's economy. Their analysis focuses particularly on five key topics: agribusiness, energy, trade, social investment, and multinational corporations"--Provided by publisher.